Improving the Quality of Healthcare Services for Patient well-being through Maqaṣid al-Sharia: a Study at Klaten Islamic Hospital - Azis, Muhammad Uqbah; Mubarok, Jaih; Kholis, Nur; Gunardi, Setiyawan (IAIN Manado, 2025)
This study aims to analyze the implementation of Maqaṣid al-Sharīah in improving the quality of healthcare services and patient well-being at Klaten Islamic General Hospital (RSUI Klaten). Using a qualitative descriptive approach through interviews, observations, and documentation, the study integrates field and library research to reveal how Sharia principles are translated into practical healthcare management. The findings show that the application of Maqasid Al-Sharia is not merely symbolic but has a measurable positive impact on service quality and patient welfare. For example, the implementation of hifz al-dīn (protection of religion) is realized through the availability of prayer facilities, halal nutrition, and spiritual counseling that enhance patients’ psychological and spiritual comfort. The principle of hifz al-nafs (protection of life) is reflected in the hospital’s patient safety centered policies and emergency response prioritization, while hifz al-māl (protection of wealth) is implemented through transparent financing and social support mechanisms using zakat and waqf funds. These initiatives collectively improve patient satisfaction, trust, and recovery outcomes, showing that Islamic ethical values can enhance both medical and moral dimensions of healthcare quality. The research also finds that the integration of Maqāṣid is an ongoing implementation process, meaning that it continues to be strengthened and expanded through staff training, Sharia governance, and digital innovation in service systems. This process reflects a continuous effort to institutionalize Islamic values within hospital operations. Overall, this study contributes to the discourse on Islamic healthcare management by providing empirical evidence that Maqasid Al-Sharia-based practices can serve as a transformative model for improving service quality and realizing comprehensive well-being (al-maṣlaḥah al-kulliyyah) in Sharia-compliant hospitals in Indonesia.